Manarang Module Based on Ethnomathematics and Augmented Reality to Enhance Students’ Metacognitive in Society 5.0 - Nursyam Anaguna; Sri Wardani; Mira; Nurtaqiya (Universitas Sulawesi Barat, 2026)
The low metacognitive abilities of students in West Sulawesi and the limited availability of digital learning media that integrate local wisdom are problems faced by teachers in the 5.0 society. The ethnomathematics and Augmented Reality (AR) approaches can be used as solutions to these problems through the use of the Mandar culture of Pattu'du Kumba dance, which contains geometric elements and philosophical values. This study aims to develop Manarang as an ethnomathematics and AR-based digital teaching module to improve students' metacognitive abilities. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants were 26 eleventh graders and one mathematics teacher. The instruments used included teacher and student response questionnaires, as well as pre-tests and post-tests validated by two validators. The results showed that the Manarang Module was valid, practical, and effective as a digital learning module on geometric transformation learning. The effectiveness assessment using the paired sample t-test (p = 0.000 < 0.05) and N-gain score of 0.62 represented a moderate improvement towards students' metacognitive skills. This product is expected to support interactive and contextual learning that is able to improve students' metacognition in realizing quality education.